2022
DOI: 10.3389/fmed.2022.811954
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Older Adults Undergoing Major Surgery: Prevalence, Association With Postoperative Cognitive Dysfunction and Potential Associated Anesthetic Agents

Abstract: BackgroundPolypharmacy, which is defined as the use of 5 or more medications, can exert significant adverse impact on older adult patients. The objective of this study was to determine the prevalence of polypharmacy, and to investigate its association with postoperative cognitive dysfunction (POCD) in older adult patients who underwent elective major surgery at Siriraj Hospital—Thailand's largest national tertiary referral center.MethodsThis prospective study included older adult patients aged ≥65 years who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Benzodiazepine receptor agonists (BZDRAs) are commonly used sedatives during the perioperative period, which can lower the consumption of intraoperative anesthetics ( Nakagawa et al, 2000 ). However, numerous studies have demonstrated that perioperative usage of BZDRAs is linked to a higher risk of POD in geriatric patients with hip fractures ( Poeran et al, 2020 ; Hernandez et al, 2021 ; Duprey et al, 2022 ; Lertkovit et al, 2022 ). The concrete mechanisms of benzodiazepine-induced POD vary based on the subtype of BZDRAs: Diazepam may affect the chloride plasticity mediated by Na + − K + − 2Cl-cotransporter isoform 1 and result in the gamma-aminobutyric acid α receptor malfunction ( Matsumoto et al, 2021 ); midazolam can alter the expression and activity of acetyl-and butyryl-cholinesterase genes ( Rump et al, 2022 ), and both contribute to benzodiazepine - induced POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Benzodiazepine receptor agonists (BZDRAs) are commonly used sedatives during the perioperative period, which can lower the consumption of intraoperative anesthetics ( Nakagawa et al, 2000 ). However, numerous studies have demonstrated that perioperative usage of BZDRAs is linked to a higher risk of POD in geriatric patients with hip fractures ( Poeran et al, 2020 ; Hernandez et al, 2021 ; Duprey et al, 2022 ; Lertkovit et al, 2022 ). The concrete mechanisms of benzodiazepine-induced POD vary based on the subtype of BZDRAs: Diazepam may affect the chloride plasticity mediated by Na + − K + − 2Cl-cotransporter isoform 1 and result in the gamma-aminobutyric acid α receptor malfunction ( Matsumoto et al, 2021 ); midazolam can alter the expression and activity of acetyl-and butyryl-cholinesterase genes ( Rump et al, 2022 ), and both contribute to benzodiazepine - induced POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In another study, the Montreal Cognitive Assessment (MoCA) was used to assess the cognitive function of elderly patients over 65 from days 5-9 after elective major surgery. The results showed that benzodiazepines and isoflurane were independent predictors of POCD (Lertkovit et al, 2022). In addition to the short-term risk of cognitive impairment, it has been reported that benzodiazepines can increase the risk of cognitive impairment years or decades later.…”
Section: Benzodiazepinementioning
confidence: 88%
“…The use of narcotic drugs may also alter the cognitive function of patients, especially the elderly, because the residual effects of drugs can modify the activity of the central nervous system. Such drugs can in uence tau protein modi cation, in ammatory process calcium regulation and mitochondrial function to alter cognitive function [20,21]. Anesthetics primarily act on the central nervous system.…”
Section: Discussionmentioning
confidence: 99%